OMNIBUS LAW METHOD IN FORMATION LOCAL REGULATION: METODE OMNIBUS LAW DALAM PEMBENTUKAN PERATURAN DAERAH - Aulia Oktarizka Vivi Puspita Sari A.P; Lintje Anna Marpaung; Rifandy Ritonga (Constitutional Law Society, 2022)
-Based on the provisions of Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning the Formation of Legislation that the omnibus law method is carried out in the planning process contained in the Regional Regulation Formation Program. The functions of regional regulations are: first, to carry out regional autonomy and co-administration, and secondly to accommodate special regional conditions and thirdly as an instrument for elaborating higher laws and regulations. Then the authority to form Regional Regulations is in the hands of Regional Governments, Regional Governments include Regional Governments. Research problems discuss the omnibus law method in forming regional regulations and the inhibiting factors of the omnibus law method in forming regional regulations. The research method uses a normative and empirical juridical approach. The results of the research on drafting laws and regulations using the omnibus law method use the process of forming laws and regulations which include the stages of planning, drafting, discussing, validating/stipulating, enacting and disseminating. And the inhibiting factor for the omnibus law method in the formation of the first regional regulations was the lack of competent drafters of laws and regulations in drafting regional laws and regulations. Second, there are no implementing regulations governing the procedures for establishing regional regulations using the omnibus law method. And third, there is no obligation for regions to use the omnibus law method in forming regional regulations.